2010
DOI: 10.1007/s10916-010-9538-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Causing Long Patient Waiting Time and Clinic Overtime in Outpatient Clinics

Abstract: This paper is focused on the factors causing long patient waiting time/clinic overtime in outpatient clinics and how to mitigate them using discrete event simulation. A two-week period of data collection is conducted in an outpatient clinic of a Singapore government hospital. Detailed time study from patient arrival to patient departure is conducted, and the possible factors causing long patient waiting time/clinic overtime are discussed. A discrete simulation model is constructed to illustrate how to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…A congested clinic increases the work load of its staff and the chances of the clinic overrunning its usual sessions. Long working hours also demotivate the clinical staff, resulting in inefficient use of resources and time [16]. Besides, congested clinics result in longer waiting times -a major cause of patient dissatisfaction.…”
Section: Contemporary Challenges Confronting Urban Outpatient Clinicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A congested clinic increases the work load of its staff and the chances of the clinic overrunning its usual sessions. Long working hours also demotivate the clinical staff, resulting in inefficient use of resources and time [16]. Besides, congested clinics result in longer waiting times -a major cause of patient dissatisfaction.…”
Section: Contemporary Challenges Confronting Urban Outpatient Clinicsmentioning
confidence: 99%
“…Their simulated result shows a 10-minute reduction in waiting time for each patient. Zhu et al [16] found that evenly distributed appointment slots could also reduce the average waiting time and clinic overtime in specialist outpatient clinics.…”
Section: Simulating Outpatient Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, a study by Le et al conducted in outpatient clinic (Trung Vuong Emergency Hospital) suggested that the average time spent from registration to doctors' conclusions was 246.87 ± 104.55 minutes (4.11 ± 1.7 hours) 9 . Accordingly, patient waiting time is influenced by various factors, such as working procedure, patient overload and appointment schedule 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Discrete event simulation is widely applied to many sections in healthcare systems such as outpatient clinic [9][10][11][12] , emergency department [13][14][15] , etc. A simulation model was constructed to predict the weekly bed occupancy rate [16] .…”
Section: Introductionmentioning
confidence: 99%